Development of an open-hardware semen homogenizer and application to serotonin effects on sperm motility - Nancy A. Juárez-Contreras; Cindy U. Rivas-Arzaluz; Oscar Gutiérrez Pérez; María E. Ayala; Andrés Aragón-Martínez (PLoS ONE, 2025)
Proper homogenization of semen samples is crucial for assisted reproductive technology (ART) and analysis of sperm motility kinematics in experimental research. Accurate homogenization ensures a consistent number of sperm per insemination in ART and uniforms number of sperm per treatment in research. Homogenization is particularly important when sperm are treated with exogenous compounds that must be evenly distributed throughout the experiment. Traditionally, semen samples are homogenized manually with a “gentle” approach or with commercial devices that are not specifically designed for this purpose. In this study, we designed, constructed, and validated an open-hardware semen homogenizer for sperm motility analysis. For validity, the hardware was used to investigate the effects of serotonin (5-HT) on boar sperm kinematics at the subpopulation level using a computer-assisted sperm analysis (CASA). All components of the homogenizer are readily available, including the STL files for the 3D-printed parts, firmware, assembly instructions, and operation guidelines. Objective homogenization was evaluated by measuring sperm density at different numbers of homogenization cycle, while “gentle” homogenization was assessed based on manual duration and inclination angle. Sperm motility kinematics showed no changes at the average level, however distinct effects emerged within subpopulations. Exposure to 5-HT differentially affected sperm motility kinematics across subpopulations displaying no change, increase or decrease in velocity indices. Under over-homogenization conditions, a clear interaction between prolonged homogenization and 5-HT exposure was observed in all subpopulations. Results suggest that objective homogenization is essential to ensure consistent sperm density, whereas over-homogenization alters sperm responses, potentially leading to biological misinterpretations.